Kebijakan Pertahanan Untuk Mencapai Sistem Keamanan Nasional - zeligke, franziska; erio kurniawan, Stalone; ginting, winardi (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
Security, derived from the Latin term "secure" which means the absence of danger, worry, includes two main methodologies, specifically conventional and unconventional security. Defense is the main tool used by a country to achieve national security, covering all aspects of national life to face various challenges. National security is concerned with maintaining the integrity and welfare of the state, society and individuals. This essay seeks to examine current security and defense threats and explain the similarities and differences in the perspective of national security. This research uses a qualitative descriptive design by conducting a comprehensive review of existing literature. This article analyzes the many risks that arise in Indonesia, including border disputes, intolerance based on ethnicity, religion, race and inter-group (SARA), disparities in administrative restructuring, law enforcement and transnational criminal activity. This study shows that the effectiveness of defense and State security has a direct impact on national resilience. A country's security is not only influenced by its security and defense measures, but also by the interaction between economic, political, legal, socio-cultural, ideological, geographic, demographic and natural resource variables.